2008
DOI: 10.1111/j.1439-0310.2008.01556.x
|View full text |Cite
|
Sign up to set email alerts
|

Why are Male Columbian Ground Squirrels Territorial?

Abstract: Male territorial defence is a component of many vertebrate mating systems and is often regarded as a tactic for acquiring mates. Traditionally considered within the context of overt site‐specific defence, territoriality actually may have several components which encompass a variety of behavioural tactics (e.g. post‐copulatory mate‐guarding, defence of resources that females need, defence of area around females) that underlie a mating system. The purpose of our study was to evaluate such influences on the terri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 50 publications
0
45
0
Order By: Relevance
“…In addition, males range widely during the mating season (Manno et al. 2007; Manno & Dobson 2008), and females that dispersed within our colony had access to most or all colony males, regardless of the location of the female’s nest burrow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, males range widely during the mating season (Manno et al. 2007; Manno & Dobson 2008), and females that dispersed within our colony had access to most or all colony males, regardless of the location of the female’s nest burrow.…”
Section: Discussionmentioning
confidence: 99%
“…Columbian ground squirrels exhibit a polygynandrous mating system (sensu Dobson et al 2010). Copulation dates for females were estimated from diagnostic behaviours that are exhibited only on the single annual day of mating (Manno et al 2007;Manno & Dobson 2008). Gestation lasts 24 days (Murie & Harris 1982) and neonates are suckled for a further 27 days of lactation.…”
Section: Field Sitementioning
confidence: 99%
“…Even though these 2-and 3-year-old males rarely defend a territory (Manno et al 2007;Manno and Dobson 2008), they are still physically capable of obtaining copulations and siring success (Raveh et al 2010). …”
Section: Operational Sex Ratiomentioning
confidence: 99%
“…Previous studies suggested that reproductive male Columbian ground squirrels invest both time and energy in postcopulatory behaviors such as mating calls (Manno et al 2007) and mate guarding (Manno and Dobson 2008). Whether such behavioral mechanisms influence siring success, however, remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Lacey & Wieczorek (2001) and Manno & Dobson (2008) obtained the location of visually observed ground squirrels by dividing their study area in non-overlapping sections with boundaries determined by the shape of the meadow, and then record the locations of each visible animal to the nearest metre on a Cartesian grid. Maher (2009) noted woodchuck Marmota monax locations with respect to the nearest burrow for which he had previously obtained GPS measures.…”
mentioning
confidence: 99%